Crude leaf extracts of piperaceae species downmodulate inflammatory responses by human monocytes - Finato, Angela Carolina [UNESP]; Fraga-Silva, Thais Fernanda [UNESP]; Uliana Carvalho Prati, Amanda [UNESP]; Alves de Souza, Amauri [UNESP]; Mazzeu, Bruna Fonseca [UNESP]; Felippe, Lidiane Gaspareto [UNESP]; Pinto, Rute Alves [UNESP]; De Assis Golim, Marjorie [UNESP]; Sueli Parreira Arruda, Maria [UNESP]; Furlan, Maysa [UNESP]; Venturini, James [UNESP] (Public Library of Science (PLoS), 2018)
In this study, we aimed to evaluate the immunomodulatory effects of crude leaf extracts from Piper gaudichaudianum Kunth, P. arboreum Aub., P. umbellata L., P. fuligineum Kunth, and Peperomia obtusifolia A. Dietr. on an in vitro model of inflammatory response. The crude extracts were previously obtained by maceration of the leaves. The half-maximal inhibitory concentration was determined by the MTT assay using human peripheral blood mononuclear cells. Human monocytes were simultaneously challenged with each crude extract and lipopolysaccharide (LPS), the major component of the outer membrane of Gram-negative bacteria, to induce a strong inflammatory response. After 24 h of incubation, cell-free supernatants were used for evaluating the mediators involved in inflammation: H2O2, TNF-α, IL-8, IL-6, IL-1β, IL-10, IL-12, FGF-b, and TGF-β1. We also compared the results with the effects of ketoprofen, a well-known anti-inflammatory drug. The P. gaudichaudianum crude extract downmodulated the production of H2O2, IL-1β, IL-6, IL-8, and TGF-β1 by LPS-stimulated monocytes; P. arboreum, IL-1β, IL-6, IL-8, and TNF-α; P. umbellata and P. fuligineum, H2O2, IL-1β, IL-6, IL-8, IL-10, and TNF-α; and P. obtusifolia, H2O2, IL-6, IL-8, IL-10, and TNF-α. In general, the crude leaf extracts amplified the anti-inflammatory response when compared with ketoprofen, particularly reducing the production of IL-8, a mediator involved in neutrophil recruitment during tissue damage. Thus, the crude leaf extracts of P. gaudichaudianum, P. arboreum, P. umbellata, P. fuligineum, and Peperomia obtusifolia elicited an anti-inflammatory response against LPS-challenged monocytes. These findings show the anti-inflammatory properties of these crude leaf extracts and offer new perspectives for their use in the treatment of inflammatory diseases.